2007
DOI: 10.1111/j.1474-919x.2007.00717.x
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of interspecific hybridization in the tracheophone suboscines: Chestnut‐naped Antpitta Grallaria nuchalis × Chestnut‐crowned Antpitta G. ruficapilla in a fragmented Andean landscape

Abstract: Based on analyses of variation in plumage, morphometrics, vocalizations, and mitochondrial and nuclear DNA sequences, we document the occurrence of interspecific hybridization between a Chestnut‐naped Antpitta Grallaria nuchalis and a Chestnut‐crowned Antpitta G. ruficapilla in a high‐elevation forest fragment in the Cordillera Central of the Andes of Colombia. One hybrid individual was collected and at least two were recorded singing. The hybrid specimen exhibits a combination of phenotypic traits that exclud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 32 publications
(31 reference statements)
1
5
0
Order By: Relevance
“…We propose that mating is strictly assortative in sympatry, and that hybridization is not a proximate cause of song convergence in our system. This conclusion is supported by previous studies as no hybrids have been found in Hypocnemis antbirds (Zimmer and Isler 2003;McCarthy 2006;Isler et al 2007), and interbreeding is very rare throughout the suboscine clade (Graves 1992;Cadena et al 2007).…”
Section: Nonadaptive Explanationssupporting
confidence: 86%
See 1 more Smart Citation
“…We propose that mating is strictly assortative in sympatry, and that hybridization is not a proximate cause of song convergence in our system. This conclusion is supported by previous studies as no hybrids have been found in Hypocnemis antbirds (Zimmer and Isler 2003;McCarthy 2006;Isler et al 2007), and interbreeding is very rare throughout the suboscine clade (Graves 1992;Cadena et al 2007).…”
Section: Nonadaptive Explanationssupporting
confidence: 86%
“…Interbreeding in birds often produces hybrids with intermediate vocal characters (Grant 1972), and this explains apparent signal convergence in some avian contact zones, particularly those involving sister species. Vocally intermediate hybrids routinely occur in clades with genetically determined songs (de Kort et al 2002; Gee 2005; Isler et al 2005; Cadena et al 2007; den Hartog et al 2007), and even in species with learnt vocalizations, including oscine passerines (e.g., Robbins et al 1986; Secondi et al 2003). In all cases, hybridization is characterized by a mix of normal song types and intermediate song types, or a gradual shift of character states (i.e., a cline).…”
mentioning
confidence: 99%
“…For example, a single captive barred antshrike ( Thamnophilus doliatus ) produced normal song after being reared in silence [7] , although it is not clear at what age it was taken into care. Similarly, one of the only known hybrid tracheophone suboscines was an antpitta ( Grallaria ) that produced a song structurally intermediate between the songs of its putative parent species [43] . This contrasts with the situation in hybrid oscines in which the structure of songs is typically unchanged from one or other of the parental song types, either because hybrid offspring copy songs from the parent male, or produce repertoires containing songs from both parental types (mixed singing) [44] [46] .…”
Section: Discussionmentioning
confidence: 99%
“…The D-statistic results indicate that 38% of triads show signals of introgression. Historically, suboscine birds were thought to exhibit relatively low hybridization rates compared to other birds (Cadena et al 2007;Graves 1992). More recently, hybridization and introgression have been found in several suboscine species (Brumfield et al 2001;Pulido-Santacruz et al 2020;Weir et al 2015).…”
Section: Introgressionmentioning
confidence: 99%